Rima dalam Nyanyian Onduo Anak Rokan di Kabupaten Rokan Hulu Riau - Nuratika Nuratika; Misra Novita; Rita Arianti; Asih Ria Ningsih; Hermawan Hermawan; Muslim Muslim (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Traditional singing as a cultural asset serves to store classical community knowledge and their views on the way of life. Traditional singing can be categorized according to its function and purpose. The Onduo Anak Rokan song is one of the traditional songs aimed at the younger generation from a set of experiences of the older group. This study aims to describe the form of rhyme in the songs of Onduo Anak Rokan in Rokan Hulu Regency, Riau Province. The research method used is descriptive qualitative. The data were obtained through interviews, observation, recording, and writing down the lyrics of the singer's song Onduo anak Rokan. The data analysis method is structural analysis which refers to Pradopo's perspective (2010) regarding rhyme forms. The results showed that there were six types of rhyme forms in Onduo anak Rokan's songs, namely initial rhyme, final rhyme, full/perfect rhyme, half/imperfect rhyme, alliteration rhyme, and asonance rhyme. The rich rhymes in Onduo Anak Rokan songs show that traditional literature has a consistent and structured aesthetic.